KUALITAS LAYANAN KETERBUKAAN INFORMASI PUBLIK BERBASIS WEBPORTAL PADA PEJABAT PENGELOLA INFORMASI DAN DOKUMENTASI (PPID) KABUPATEN SLEMAN TAHUN 2019 - Coni Wanprala; Isnaini Muallidin; Dewi Sekar Kencono (Kybernan: Jurnal Studi Kepemerintahan, 2020)
At present the development of technology and information has reached a very rapid level. Technology and information are used as a service media in the government environment which is also known as e-Government, one of which is the service of public information disclosure. The central government through Law No. 14 of 2008 concerning Openness of Public Information, encourages all Public Agencies including the Sleman Regency Government to make transparency in the administration of the state by utilizing information technology. This research is a qualitative descriptive study which aims to describe the reality that occurs. The object of research in this study is the official website of the Information and Documentation Management Officer (PPID) of Sleman Regency with the domain https://ppid.slemankab.go.id then the Sleman Regency Communication and Informatics Office as the organizer of the public information disclosure program. The data collection technique itself is carried out by means of interviews, documentation studies, and field observations (observations). After collecting and presenting data, then the data will be reduced first then analyzed and concluded. From the results of the study, in general the researchers concluded that the Sleman Regency PPID website had reached the level of qualification to become a quality website, however there were still some improvements and evaluations that had to be done by the relevant agencies in order to be better, namely (i) the website was still being assessed as a one-way service (ii) There are still many OPDs that are not ready to implement PPID (iii) data and information are still not updated (iv) lack of responsiveness of services in requests for information.